2006
DOI: 10.1007/s11882-006-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil function in eosinophil-associated gastrointestinal disorders

Abstract: Eosinophil-associated gastrointestinal disorders (EGIDs) are characterized by a rich eosinophilic inflammation of the gastrointestinal tract in the absence of known causes for eosinophilia or other gastrointestinal disorders. These disorders include eosinophilic esophagitis, eosinophilic gastritis, eosinophilic gastroenteritis, eosinophilic enteritis, and eosinophilic colitis, and are being recognized with increasing frequency. Clinical studies suggest that eosinophils have a pathogenic role in EGID; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 55 publications
0
35
0
1
Order By: Relevance
“…The SCIDbgMN mice utilized in these experiments were created from SCIDbg mice after X irradiation (4 Gy) and other treatments (anti-Ly6G MAb and carrageenan). Since irradiation is known to damage the intestinal epithelium, there was a concern that intestinal epithelial cellmediated innate immune responses (e.g., antimicrobial peptide production and cytokine/chemokine production) would be impaired in SCIDbgMN mice and the susceptibility of these (47), the accumulation of these cells at the inflammation site has been described (20,55). So far, the active pathological role of these cells at the C. parvum infection site is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The SCIDbgMN mice utilized in these experiments were created from SCIDbg mice after X irradiation (4 Gy) and other treatments (anti-Ly6G MAb and carrageenan). Since irradiation is known to damage the intestinal epithelium, there was a concern that intestinal epithelial cellmediated innate immune responses (e.g., antimicrobial peptide production and cytokine/chemokine production) would be impaired in SCIDbgMN mice and the susceptibility of these (47), the accumulation of these cells at the inflammation site has been described (20,55). So far, the active pathological role of these cells at the C. parvum infection site is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 2 PU.1 sites, a C/EBP␣ site, and, importantly, a GATA-1 site were also present, suggesting that transcription factors that play crucial roles during eosinophil differentiation may reinforce the IL-5R/syntenin pathway. 38,39 In an analogous fashion, transcription factors that control T helper cell differentiation have been shown to stimulate expression of factors that control their own activation. [40][41][42][43] We propose a model in which IL-5 via IL-5R␣/syntenin stimulates key eosinophil transcription factors, which in turn reinforce IL-5R␣ and syntenin expression as part of a positive feedback mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…These data demonstrate that IL-13 supports eosinophil migration and that CCL11 and CCL24 also are both important in promoting eosinophil infiltration [66,67] . Although patients with EoE have higher levels of several cytokines, the cytokines that are most consistently increased in this allergic disease are IL-5, IL-13 and eotaxin-3 (CCL26) [68,69] . Genome-wide microarray expression studies have shown that the gene-encoding eotaxin-3 is the most highly induced gene in EoE patients compared to healthy individuals [43] .…”
Section: Genetic Vs Environmental Etiological Factorsmentioning
confidence: 99%